2022
DOI: 10.1186/s13023-022-02595-0
|View full text |Cite
|
Sign up to set email alerts
|

The psychosocial situation of families caring for children with rare diseases during the COVID-19 pandemic: results of a cross-sectional online survey

Abstract: Background The COVID-19 pandemic is affecting many areas of life and has posed additional strains on the highly vulnerable group of caregivers of children with rare diseases (RDs). The psychosocial situation of the family caregivers deserves more attention, both in research and practice. The current study explores the distress level of caregivers of children with RDs, their psychosocial information needs, and caregiver-reported health-related quality of life (HRQoL) of children with RDs in time… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 60 publications
2
18
0
Order By: Relevance
“…In comparison to another study in highly vulnerable group of children with rare diseases, a study by Rihm et al also reported a high psychosocial burden in caregivers and reduced quality of life in children with rare diseases. 51 A similar trend was also observed in both caregivers and children with type 1 diabetes. 52…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…In comparison to another study in highly vulnerable group of children with rare diseases, a study by Rihm et al also reported a high psychosocial burden in caregivers and reduced quality of life in children with rare diseases. 51 A similar trend was also observed in both caregivers and children with type 1 diabetes. 52…”
Section: Discussionsupporting
confidence: 60%
“…In comparison to another study in highly vulnerable group of children with rare diseases, a study by Rihm et al also reported a high psychosocial burden in caregivers and reduced quality of life in children with rare diseases. 51 A similar trend was also observed in both caregivers and children with type 1 diabetes. 52 A study by Kim et al 53 also reported an increased risk of children sleep and behavioral problems related to parents' stress and depression during the pandemic.…”
Section: Impact Of Parents' Mental Health Status Toward Childrensupporting
confidence: 60%
“…As children with IF face many challenges at baseline and are shown to have a lower HRQoL than healthy children, the pandemic may add to that burden 4 . However, only a few studies were focusing on chronically ill children and so far, none had addressed the caregivers perceived impact in patients with IF during the pandemic 17–19 . In our study, a high rate of caregivers stated a negative impact on their child's QoL and HRQoL without a significant difference between children with IF, IBD or otherwise HC.…”
Section: Discussionmentioning
confidence: 54%
“…The geographical distribution of data in the studied material showed a prevalence of research in continental Europe, with 61.1% of the total yield of studies coming from this region. Of these ten documents, five were from England [9,10,14,23,24], three were from Italy [5,7,11], two were from Germany [8,25], and one was from Norway [13]. After Europe, two articles were from North America [12,18], one was from Asia (Hong Kong) [26], one was from the Asia-Pacific region [17] (based on data from Australia, Hong Kong, India, Japan, China, Malaysia, New Zealand, the Philippines, Singapore, and Taiwan), one was from South America (Brazil) [6], and, finally, there was one that took a broad global perspective [19].…”
Section: Resultsmentioning
confidence: 99%
“…We searched the Google Scholar, PubMed, and Scopus databases using 'COVID-19', 'rare diseases', and 'psychology' as keywords, which yielded 217 articles in Google Scholar, 11 in Scopus, and 7 in PubMed. Many of the selected articles examined the impact of COVID-19 on loneliness [5][6][7][8], social isolation [7,9,10], depressive moods [6][7][8]10], distress [7,8,11,12], and anxiety [7][8][9][10]13] in patients with RDs, the people involved with them, and the psychological burden the disease imposed [8,14]. Loneliness and social isolation, although different, are often connected and are already an important social problem, which the pandemic exacerbated [15], especially for the most fragile people in society.…”
Section: Introductionmentioning
confidence: 99%